2023
DOI: 10.1002/smll.202304881
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Ligand on the Biocompatibility of InP/ZnS Quantum Dots with Platelets

Hélio M. Gil,
Zoe Booth,
Thomas W. Price
et al.

Abstract: InP/ZnS quantum dots (QDs) have received a large focus in recent years as a safer alternative to heavy metal‐based QDs. Given their intrinsic fluorescent imaging capabilities, these QDs can be potentially relevant for in vivo platelet imaging. The InP/ZnS QDs are synthesized and their biocompatibility investigated through the use of different phase transfer agents. Analysis of platelet function indicates that platelet‐QD interaction can occur at all concentrations and for all QD permutations tested. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Importantly, in this review, we explored the beneficial, potential roles of QDs in the haematopoietic system, from the prevention of plaque growth in atherosclerotic mice models [32], the use of red blood cells in QD chemotherapy [52], and effective imaging of damaged endothelium [8] and HSCs [76]. However, we have also delved into the potential harm and lack of biocompatibility of QDs on the haematopoietic system, from deformation and haemolysis in red blood cells [49], differing findings on the inflammatory responses of leukocytes [59,60], activation of platelets [14,41], and changes to the coagulation cascade [45][46][47]. Given the need of the vascular system for the delivery of QDs to areas of the biological system, further research is greatly needed to establish the differing effects of the different makeups that QDs can have, from shell to ligands, to provide a safe therapeutic or diagnostic agent for use within a medical environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, in this review, we explored the beneficial, potential roles of QDs in the haematopoietic system, from the prevention of plaque growth in atherosclerotic mice models [32], the use of red blood cells in QD chemotherapy [52], and effective imaging of damaged endothelium [8] and HSCs [76]. However, we have also delved into the potential harm and lack of biocompatibility of QDs on the haematopoietic system, from deformation and haemolysis in red blood cells [49], differing findings on the inflammatory responses of leukocytes [59,60], activation of platelets [14,41], and changes to the coagulation cascade [45][46][47]. Given the need of the vascular system for the delivery of QDs to areas of the biological system, further research is greatly needed to establish the differing effects of the different makeups that QDs can have, from shell to ligands, to provide a safe therapeutic or diagnostic agent for use within a medical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets spread on fibrinogen after incubation with QDs were seen to have normal adherence whilst surface area was decreased with high concentration of LA and GSH coatings. The study concluded that both the concentration and coating of QDs have differing effects on platelets and this needs to be considered before implementation into a biological system [14].…”
Section: Direct Platelet-qd Interactionsmentioning
confidence: 99%
See 1 more Smart Citation